Start Here, Or Here, No Here: Introductions to Rethinking Education Policy and Methodology in a Post-Truth Era - Jennifer R. Wolgemuth; Mirka Koro-Ljungberg; Travis M. Marn; Anthony J. Onwuegbuzie; Shaun M. Dougherty (Arizona State University, 2018)
This special issue takes up urgent questions about how we education scholars might think and do policy and methodology in what has come to be known as the post-truth era. The authors in this special issue grapple with questions about the roles and responsibilities of educational researchers in an era in which research and policy have lost their moorings in T/truth. Collectively they reconceptualize educational research and policy in light of post-truths, anti-science sentiment, and the global rise of right-wing populism. At the same time we editors wonder whether post-truth is given a bad rap. Could post-truth have something productive to offer? What does post-truth open up for educational research and policy? Or, is the real issue of this special issue a collective despair of our own insignificance and obsolescence in the wake of post-truth. Whatever we editors and authors aimed to do, this special issue will not be heard by post-truth adherents and partisans. Perhaps its only contribution is encouragement to stay with the troubles of a post-truth era, even as we despair the consequences of our research and policy creations.